INDICATION, PROGNOSTIC FACTORS AND RESULTS OF SURGICAL TREATMENT FOR LUNG PARENCHYMAL LACERATION AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the indications, prognostic factors, and surgical outcomes in patients with lung parenchymal laceration.Methods: A retrospective descriptive study was conducted on 42 patients with lung parenchymal laceration who underwent surgery at the Cardiovascular and Thoracic Center, Viet Duc University Hospital, from December 2020 to December 2024. Epidemiological characteristics, injury mechanisms, CT findings, surgical indications and techniques, postoperative outcomes, and prognostic factors were analyzed. Results: Male patients predominated (69.0%), with a mean age of 35.6 ± 16.3 years. Traffic accidents were the leading cause (78.6%). Upon admission, 28.6% of patients were comatose, 33.3% had respiratory failure, and 23.8% were in shock. CT imaging showed that 90.5% of injuries were classified as type 3 according to Wagner’s classification. The main surgical indication involved grade IV–V ruptures (64.3%). Surgical techniques included lobectomy (47.7%), parenchymal repair (42.9%), and wedge resection (21.4%). Video-assisted thoracoscopic surgery (VATS) was performed in 64.3% of cases, resulting in shorter operative time, reduced blood loss, and shorter drainage duration compared with thoracotomy. Postoperative outcomes were favorable in 80.9% of patients. Complications included atelectasis (11.9%), prolonged air leak (7.1%), reoperation (7.1%), and mortality (9.5%).Conclusions: Surgical treatment of pulmonary parenchymal rupture yields favorable outcomes with a low complication rate. VATS represents an effective, minimally invasive approach that reduces surgical trauma and enhances recovery. Poor prognostic factors include blood loss >1500 mL, severe shock, ISS >25, and respiratory failure on admission, emphasizing the importance of early detection and timely management.
Keywords: Lung parenchymal laceration, blunt chest trauma, thoracoscopic surgery, prognostic factors.